Kontribusi Green Human Resource Management Terhadap Pembentukan Perilaku Hijau di Kalangan Karyawan - Thea Geneveva Josephine Jesajas; Puty Febriasari; Ali Afif (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2026)
This study is motivated by environmental changes that drive organizations to demonstrate greater concern for their surroundings, which has become a global challenge, particularly in Southeast Asia. Green Human Resource Management (GHRM) is regarded as a strategic approach to promoting sustainability through human resource practices that encourage environmental awareness. The objective of this research is to examine the relationship between GHRM, environmental knowledge, and employee green behavior. A quantitative research method was employed, with respondents comprising employees from both private and public sectors in West Kalimantan. Data were analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS). The findings indicate that discriminant validity was achieved (HTMT < 0.9), with R² values of 0.470 for employee green behavior and 0.353 for environmental knowledge, both categorized as weak. All hypotheses were supported (p-value < 0.05), and environmental knowledge was found to partially mediate the relationship between GHRM and employee green behavior (p-value = 0.000). These results suggest that implementing GHRM within organizations can enhance employees’ environmentally friendly behavior, even when their environmental knowledge is limited, providing strategic implications for fostering a strong sustainability-oriented organizational culture.